2004
DOI: 10.1111/j.0906-6705.2004.00221.x
|View full text |Cite
|
Sign up to set email alerts
|

Narrow‐band ultraviolet‐B stimulates proliferation and migration of cultured melanocytes

Abstract: Narrow-band ultraviolet-B (UVB) radiation is an effective treatment for vitiligo vulgaris. However, the mechanisms of narrow-band UVB in inducing repigmentation of vitiligo lesions are not thoroughly clarified. The purpose of our study was to investigate the effects of narrow-band UVB irradiation on melanocyte proliferation and migration in vitro. Our results showed that the cell counts as well as [3H]thymidine uptake of melanocytes were significantly enhanced by narrow-band UVB-irradiated keratinocyte superna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
83
1
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(92 citation statements)
references
References 44 publications
7
83
1
1
Order By: Relevance
“…(3) Matrix metalloproteinase-2 (MMP-2) is known to enhance migration of melanocytes from adjacent normal skin. Previous study showed that NB-UVB irradiation could significantly increase the activity of MMP-2 in melanocytes [16]. Dermabrasion using fractional Er:YAG laser followed by NB-UVB irradiation would enhance the stimulation of MMP-2 activity in vitiligo lesion.…”
Section: Discussionmentioning
confidence: 89%
“…(3) Matrix metalloproteinase-2 (MMP-2) is known to enhance migration of melanocytes from adjacent normal skin. Previous study showed that NB-UVB irradiation could significantly increase the activity of MMP-2 in melanocytes [16]. Dermabrasion using fractional Er:YAG laser followed by NB-UVB irradiation would enhance the stimulation of MMP-2 activity in vitiligo lesion.…”
Section: Discussionmentioning
confidence: 89%
“…Ultraviolet B rays cause DNA damage and formation of pyrimidine dimmers [15]. In addition to T cell apoptosis, UVB radiation triggers changes in cytokine production, local immunosuppression and stimulation of melanocyte-stimulating hormone (MSH), and increases migration, proliferation of melanocytes and melanogenesis [16,17]. A twostep effect of NB-UVB has been proposed -both of them may occur simultaneously though.…”
Section: Mechanism Of Actionmentioning
confidence: 99%
“…In another study Wu et al investigated affects of NBUVB on melanocytes proliferation in vitro and they observed a significant increase in bFGF and in endothelin-1 (ET-1) release as bFGF is a natural mitogen for melanocytes and ET-1 can stimulate DNA synthesis in melanocytes. They also suggested that matrix metalloproteinase-2 (MMP-2) activity play important roles in narrow-band UVB-induced migration of melanocytes [36]. In a recent study, Starner et al showed that UVR radiation stimulates prostoglandin E2 (PGE2) secretion in melanocytes that leads cAMP production, tyrosinase activity and proliferation in melanocytes [37].…”
Section: Ultraviolet Radiationmentioning
confidence: 99%